Government Health Financing in India : Challenges in Achieving Ambitious Goals - Berman, Peter; Ahuja, Rajeev; Tandon, Ajay; Sparkes, Susan; Gottret, Pablo (World Bank, Washington, DC, 2013)
The Government of India has publicly committed to a doubling or trebling of government health spending by 2012 and launched a major program, the National Rural Health Mission (NRHM), to help spend the additional funds and achieve better health outcomes. This paper reviews recent data on trends in government spending and various scenarios of central and state funding to assess the feasibility of achieving these financing goals. The goal of 2 percent of Gross Domestic Product (GDP) for government health spending is unlikely to be achieved, although there is clear evidence of program growth. Much larger state-level spending is needed to accelerate overall government spending in India's federal system. In addition, there is evidence of constraints in the ability to spend significantly increased budgets in a timely way and possible state substitution of increased central funding for existing state budgets. Significantly increasing government health spending in India requires more than simply raising budgets at the central level. NRHM does show some positive effects, but the rapid gains envisaged will require greater efforts to address the shortcomings of government systems and creative approaches to India complex federal financing system.